Are Social and Ethnic Reading Inequalities Increasing During School Closures?—The Mediating Role of Parental Involvement in Distance Learning - Weber, Christoph; Helm, Christoph; Kemethofer, David (Frontiers in Education, 2021)
From spring 2020 many countries throughout Europe and beyond temporarily closed schools to tackle the spread of the coronavirus. First studies indicate that these school closures resulted in lower learning gains compared to learning gains in preceding years and widened social and ethnic disparities by affecting disadvantaged students more strongly than their more advantaged peers. Moreover, during school closures, parental involvement in distance learning is regarded as crucial for successful learning, especially for younger children. In the current study, we examine whether social and ethnic disparities in the reading achievement of primary school students widened during COVID-related school closures in spring 2020 and whether increased disparities are mediated by parental involvement in distance learning. We use data from 409 Austrian 2nd graders, whose teachers participated in an ongoing study on the use of learning progress assessment. Adopting a within-subject design, we first compare the effects of social and ethnic family background on reading achievement during a pre-lockdown period with the respective effects during a peri-lockdown period of similar length. Controlling for pre-lockdown reading differences, we found that low socioeconomic status and non-German language use at home negatively predicted post-lockdown reading achievement, indicating that post-lockdown disparities were larger than expected due to disparities at pre-lockdown. In contrast, we found no such effects during the instruction-as-usual pre-lockdown period. Second, a series of mediation models did not provide any support for the hypothesis that parental involvement accounted for family background effects on reading achievement during the peri-lockdown period.